Exact equatorial water waves in the f-plane. (April 2016) - Henry, David
Abstract: We present an exact solution for geophysical ocean waves in the Equatorial region which is three-dimensional, nonlinear, explicit in the Lagrangian formulation, and which incorporates a meridional current that is transverse Equatorial.